IMPLEMENTASI JUST IN TIME DALAM MENINGKATKATKAN PRODUKTIVITAS EFISIENSI BIAYA PRODUKSI - Hakim, Luqman (Journal of Research and Technology, 2015)
The purpose of Just In Time (JIT) is to increase productivity and reduce production costs by eliminating dissipation that exist in the company through continuous improvement activities, and the purpose of this study was to determine the implementation of JIT in increasing productivity and cost efficiency of production in manufacturing companies. The research stages research are 1) identify problems 2) data used in this research are quantitative data and qualitative data, 3) the collection and processing of production and purchasing data, 4) the implementation of JIT system, 5) eliminate the dissipation and the available participation of employees, 6) reduce or eliminate defect products. The results of this research indicate that the implementation of JIT can improve company productivity and efficiency of the production costs.